FORMULATION AND EVALUATION OF HERBAL GEL CONTAINING LANTANA CAMARA LEAVES EXTRACT - Pawar, Deepak P; Shamkuwar, Prashant B (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Herbal medicine has become an item of global importance both medicinal and economical. Although usage of these herbal medicines has increased, their quality, safety and efficiency are serious concerns in industrialized and developing countries. Herbal remedies are getting increasing patient compliance as they are devoid of typical side effects of allopathic medicines. Â Â Â Â Â Â Â Â The present research has been undertaken with the aim to formulate and evaluate the herbal gel containing Lantana camara leaf extract. The gel formulation was designed by using Carbapol 940, Lantana camara leaf extract, propylene glycol, methyl paraben, propyl paraben and required amount of distilled water. The skin pH (6.8-7) was maintained by drop wise addition of Tri-ethanolamine. The physicochemical Parameters of formulations (pH, Spreadibility, Stability etc.) were determined. Stability studies have carried out as per ICH guidelines for 3 months at different temperatures and humidity. The results showed that formulation containing Lantana camara leaf extract Show better stability. Further formulations have studied for skin irritation on animal model (Rat) and result showed that there was no skin irritation to animals. Our literature survey revealed that the herbal gel of Leaves extracts from leaves of Lantana Camara was not investigated; hence these activities have been investigated in the present study. Â Key words: Lantana camara, hydroalcoholic extract, Carbapol 940, Gel